Emerging infectious diseases of plants : Pathogen pollution, climate change and agrotechnology drivers - Anderson, Pamela K.; Cunningham, A.A.; Patel, NG; Morales, Francisco José; Epstein, PR; Deszak, P (Elsevier, 2004)
Emerging infectious diseases (EIDs) pose threats to conservation and public health. Here, we apply the definition of EIDs used in the medical and veterinary fields to botany and highlight a series of emerging plant diseases. We include EIDs of cultivated and wild plants, some of which are of significant conservation concern. The underlying cause of most plant EIDs is the anthropogenic introduction of parasites, although severe weather events are also important drivers of disease emergence. Much is known about crop plant EIDs, but there is little information about wild-plant EIDs, suggesting that their impact on conservation is underestimated. We conclude with recommendations for improving strategies for the surveillance and control of plant EIDs.